INCREASING OF METAL RECOVERY IN LEACHING PROCESS OF SPENT CATALYST AT LOW TEMPERATURE: THE ADDITION OF HYDROGEN PEROXIDE AND SODIUM CHLORIDE - Kevin Cleary Wanta; Edward Yonathan Natapraja; Ratna Frida Susanti; Gelar Panji Gemilar; Widi Astuti; Himawan Tri Bayu Murti Petrus (Metalurgi, 2021)
One of the factors that affect the leaching process of a mineral source is the mineral characteristics of the raw materials. Not all mineral phases can be leached directly and completely. Thus, some minerals require special treatment so that the leaching process can take place optimally. This study will focus on studying the effect of additive compounds addition, i.e. hydrogen peroxide and sodium chloride, in the leaching process of spent catalyst using a sulfuric acid solution. The leaching process was carried out at a concentration of 1 M sulfuric acid solution for 240 minutes at room temperature. The hydrogen peroxide concentration was varied at 0–9%v/v, while the sodium chloride concentration was varied at 0–0.8 mol/L. The experimental results showed that the two additive compounds were able to increase nickel recovery significantly. The highest nickel recovery of 95.08% was achieved when hydrogen peroxide was used at 9%v/v. The nickel recovery is 3.5 times higher than without the addition of hydrogen peroxide. Meanwhile, sodium chloride concentration of 0.8 mol/L was able to provide the highest nickel recovery of 50.38% or an increase of 1.9 times compared to without the addition of sodium chloride.